PENGOLAHAN FOTO UDARA DRONE MENGGUNAKAN PERANGKAT LUNAK Pix4DMAPPER (Drone Aerial Photograph Processing Using Pix4D Mapper Software) - Arthur Gani Koto (Universitas Muhammadiyah Gorontalo, 2021)
Abstract - A recording project using a drone where one of the results is in the form of aerial photographs, it is necessary to carry out further processing, namely a mosaic to obtain the final result in the form of an orthomosaic. It is intended that it can be analyzed for various interests, especially in the field of earth. This study aims to show how to process drone aerial photos into orthomosaic using a desktop PC that has Pix4Dmapper software installed. The data used is an aerial photo of the PRPM area